Educational Programs in Entrepreneurship for Bachelor Degree Students and Requirements to Their Implementation - Yu. B. Rubin (Высшее образование в России)
The article describes a practical approach to design content of entrepreneurship education programs for bachelor degree students and different learning courses in order to form necessary competencies for professional doing business. As well the author outlines the requirements to institutional conditions of teaching process in Entrepreneurship education for bachelor degree students related to the quality of learning courses, the competencies of academic staff, practical training, learning infrastructure.